Masyarakat Cerdas Tabungan Berkembang Melalui Kecakapan Digital Dan Keuangan Di Era Fintech - Khoerunnisa, Tia; Kartika, Sri; Maulana, Asep (Ridwan Institute, 2025)
Digital transformation has reshaped how individuals manage their finances, including saving behavior in the fintech era. However, technological advancement is not always accompanied by sufficient digital and financial literacy, resulting in suboptimal financial behavior among society. This study aims to analyze the influence of digital literacy and financial literacy on saving behavior among Indonesian users of digital financial services. This research employed a quantitative approach with an explanatory research design and purposive sampling technique involving 110 respondents who have used fintech applications such as OVO, DANA, GoPay, or mobile banking. Data were collected using an online questionnaire and analyzed through multiple linear regression with SPSS version 27. The findings reveal that financial literacy has a positive and significant effect on saving behavior, while digital literacy has no significant effect. However, both variables simultaneously show a significant influence on saving behavior with a contribution of 51.6%. These results highlight that financial literacy plays a dominant role in shaping saving habits in the digital era, while digital literacy acts as a supportive factor that enhances financial behavior effectiveness. The study recommends promoting digital-based financial education to strengthen public literacy and financial independence.